Restoring Victims of Wrongful Arrest: Automatic Compensation through a Parallel Justice Approach - Susilo, Erwin; Negara, Dharma Setiawan; Lufsiana, Lufsiana (Universitas Islam Sultan Agung, 2025)
This study aims to analyze the weaknesses of the existing compensation mechanism for victims of wrongful arrest in the criminal justice system and to propose a reform model based on the principle of Parallel Justice (PJ). Although Indonesian law, particularly the Criminal Procedure Code and Government Regulation No. 92/2015, already provides a legal basis for compensation, the mechanism remains petition-based and dependent on victims’ initiative through pre-trial proceedings. Such a passive system creates structural injustice and fails to guarantee effective recovery for victims of state error. The research method used in this study is normative legal research, employing statutory, conceptual, and comparative approaches. The statutory approach is applied to examine the positive law in Indonesia regarding compensation. The conceptual approach is used to analyze and reformulate the theory of compensation by incorporating the PJ framework developed by Susan Herman, which emphasizes proactive victim restoration. The comparative approach reviews practices in other jurisdictions such as Germany, the Netherlands, Italy, and the United States to identify models of automatic compensation that can be adapted into the Indonesian context. The novelty in this research is the application of the Parallel Justice concept—originally designed for crime victims in general—to the context of wrongful arrest caused by state authorities. This adaptation provides a new paradigm in Indonesian criminal procedure by positioning victims of wrongful arrest not merely as claimants but as individuals entitled to automatic state responsibility. Based on the research, it is concluded that adopting the PJ approach can create a more responsive, victim-oriented, and automatic compensation system. Such reform would strengthen the protection of human rights, enhance public trust in the legal system, and ensure that victims of wrongful arrest are restored fairly, quickly, and comprehensively.